Building the Science Base for Dental Public Health - Scott L. Tomar, DMD, DrPH (Blackwell Synergy, 2002)
The Journal of Public Health Dentistry is in its 62nd year as the official publication of the American Association of Public Health Dentistry (AAPHD), the world’s largest organization devoted to the advancement of dental public health practice, training, and research. This journal serves several functions, including communicating the proceedings of AAPHD’s annual meetings/ providing a forum for relevant commentaries, serving as an outlet for reports of innovative and successful public health initiatives, and publishing scientific articles on dental public health topics. We also publish the proceedings of the annual meeting of the American Board of Dental Public Health, provide a permanent record of the Knutson Award ceremony of the American Public Health Association‘s Oral Health Section, and mark sign&- cant events in the professional lives of AAPHD members through the Archives